Peran Pelaksanaan Kegiatan Pendukung Bimbingan Dan Konseling Di Sekolah - Hilmia, Hilma; Nisa, Khairun; Azzahra, Renita; Ikmala, Putri; Sunarti , Titi (Jurnal Ilmu Sosial dan Humaniora, 2026)
Guidance and counseling (BK) is a service that helps students understand themselves and adjust to school, home, and the community. The purpose of this paper is to analyze the role of support activities in improving the effectiveness of BK services in schools. These activities include the use of instruments, data collection, case meetings, home visits, case transfers, and literature references. The analysis shows that support activities are crucial in helping BK teachers collect objective data, understand students' conditions holistically, and design services tailored to their needs. Furthermore, these activities have a positive impact on students' personal, social, academic, and career development. With proper planning, BK services can be implemented more effectively and professionally. Therefore, BK support activities are a vital component for optimal student development and independence.